Influence on drug efficacy of the binding behavior of pioglitazone hydrochloride with tryptophan residues, and tyrosine residues in bovine transferrin. Issue 10 (26th November 2018) - Liu, Bao-Sheng; Wang, Chun-Dan; Bian, Gang; Ma, Li-Hua; Zhang, Hong-Cai; Cheng, Xu
Abstract: The interaction of pioglitazone hydrochloride bound to tryptophan residues and tyrosine residues in bovine transferrin was investigated using synchronous fluorescence spectroscopy at various temperatures (298, 310, and 318 K). From binding constants and thermodynamic parameters, it was shown that 1:1 stable compound was formed by the electrostatic force interaction of pioglitazone hydrochloride bound to tryptophan residues and tyrosine residues in bovine transferrin. The extent of binding between pioglitazone hydrochloride and tryptophan residues in bovine transferrin was more than that between pioglitazone hydrochloride and tyrosine residues in bovine transferrin. At 310 K, the fluorescence quenching ratio number of tyrosine residues and tryptophan residues in bovine transferrin were 47.52% and 54.19%, respectively, which indicated that the fluorescence contribution of tryptophan residues was greater. At 310 K, pioglitazone hydrochloride-tyrosine residues(in bovine transferrin) binding rate were 55.60–73.82%, and the combined model was W  = −0.0315 R 2  − 0.1520 R  + 0.7385. The value of Hill's coefficients was greater than 1, which suggested that there was a positive cooperativity between pioglitazone hydrochloride and subsequent ligands. The results of molecular docking were consistent with that of experimental calculation.